Myofunctional Therapy for the Treatment of Obstructive Sleep Apnea: Systematic Review and Meta-Analysis - Lucas Gabriel dos Anjos Ferreira; Vanessa Souza Gigoski de Miranda; Maria Eduarda Pedroso Baseggio; Miriam Allein Zago Marcolino; Deisi Cristina Gollo Marques Vidor (International Archives of Otorhinolaryngology)
Introduction Given the severity with which obstructive sleep apnea (OSA) syndrome can affect the patient's health, many therapies have been presented to minimize the occurrence of episodes of airway obstruction during sleep. Regarding non-invasive and effective methods, orofacial myofunctional therapy (OMT) is an important adjuvant in the clinical treatment.